Solve the following ordinary differential equations:
d²y/dx²+dy/dx+y=0
For solving equation : "y^{(2)}+y^{(1)}=-y" .
The solution is "y=e^{q*x}" .
By substituting such expression into the differential equation can be formulated as the equation on "q" : "(q^{2} + q - 1)*e^{q*x}=0" .
Where we substitute: "y^{(2)} = q^{2}*y" and "y^{(1)} = q" .
"e^{q*x} \\neq 0" as the exponential function will always be non-zero for any finite "x" so zeros must come from:
"q^2 + q + 1 =0"
solution of obtained equation is
"q_{+,-} = -\\frac{1}{2} \\pm \\frac{i 3^{1\/2}}{2}"
so solutions of the equation are
"y_{+,-} = C_{+,-}* exp(-\\frac{1}{2} \\pm \\frac{i 3^{1\/2}}{2})"
And the general solution of equation is
"y = C_{+}* exp(-\\frac{1}{2} + \\frac{i 3^{1\/2}}{2}) + \ufeffC_{-}* exp(-\\frac{1}{2} - \\frac{i 3^{1\/2}}{2})"
also the general solution can be presented in the trigonometrical form, by substituting the formula into Euler's identity "e^{(a+i*b)}=e^a(\\cos{b}+i*\\sin{b})" the general solution will be given by
"y = C_{1}* e^{-\\frac{x}{2}}*\\sin{ \\frac{\\sqrt{3}}{2}x} + \ufeff C_{2}* e^{-\\frac{x}{2}}*\\cos{ \\frac{\\sqrt{3}}{2}x}"
Comments
Leave a comment